2021
DOI: 10.3390/educsci11020081
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Slovak Students on Distance Online Learning in the Time of Coronavirus—A Preliminary Study

Abstract: Teaching and learning at educational institutions in Slovakia has been based on traditional education, consisting of face-to-face classes until it was disrupted by the spread of the Coronavirus disease. A sudden lockdown caused massive changes, which presented challenges not only for teachers, but also for students who were forced to adapt their learning in a very short time, without any previous preparation. Since various educational institutions were forced to remain closed, they had no option but to shift f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…Students' deepened understanding was cited in a number of studies and related to subject content (e.g., Nugraha et al, 2021) and their ability to discuss and communicate topics effectively (e.g., Bruin, 2020). Characteristic approaches of online learning also helped increase understanding (Nurliani et al, 2021;Poláková & Klímová, 2021), such as the use of videos (e.g., Rusmansyah et al, 2021) and flipped feedback (e.g., Education Scotland, 2021). In a study of Maths students in the United Arab Emirates, Almarashdi and Jarrah (2021) found that students were focused more on developing their understanding of concepts, rather than on memorising answers for tests during remote online learning.…”
Section: Cognitive Engagementmentioning
confidence: 99%
“…Students' deepened understanding was cited in a number of studies and related to subject content (e.g., Nugraha et al, 2021) and their ability to discuss and communicate topics effectively (e.g., Bruin, 2020). Characteristic approaches of online learning also helped increase understanding (Nurliani et al, 2021;Poláková & Klímová, 2021), such as the use of videos (e.g., Rusmansyah et al, 2021) and flipped feedback (e.g., Education Scotland, 2021). In a study of Maths students in the United Arab Emirates, Almarashdi and Jarrah (2021) found that students were focused more on developing their understanding of concepts, rather than on memorising answers for tests during remote online learning.…”
Section: Cognitive Engagementmentioning
confidence: 99%
“…In the context of higher education, the pandemic promoted the implementation of online learning systems and the training of instructors to teach online. In other words, studies conducted during this pandemic could present practical implications for future online learning systems and models [8].…”
Section: Online Learning and Emergency Remote Teaching (Ert)mentioning
confidence: 99%
“…Higher education in many countries was forced to switch to ERT on that day or roughly around the same time. Since the outbreak of COVID-19, there has been a growing body of literature that explores students' ERT experiences in many parts of the world such as Jordan [4], the US [5], Serbia [6], South Africa [7], Slovakia [8], the UK [9,10], and Hong Kong [11]. However, these studies focus on students in general with no special attention to international students.…”
Section: Introductionmentioning
confidence: 99%
“…However, student responses to the rapid transition to online learning may also be influenced by their own digital literacy. According to Poláková and Klímová (2021), students are ready and have the necessary skills to use technology for education. In addition, Jin et al (2021) found that students discovered the convenience of online learning as a result of the emergency response of universities to the global COVID-19 pandemic.…”
Section: Review Of Literaturementioning
confidence: 99%